2013
DOI: 10.5505/tjtes.2013.14306
|View full text |Cite
|
Sign up to set email alerts
|

Should apendectomy be performed at amyand's hernia? Two case report

Abstract: ÖZETFıtık kesesi içerisinde apendiks vermiformis bulunması Amyand hernisi olarak adlandırılır. Hastalık ismini İlk kez 1735 yılında tanım-layan Claudius Amyand'dan almıştır. Yetişkinlerde görülme sıklığı %0.51-%1 olarak bildirilmiş olmasına rağmen çocuk hasta grubunda olgu azlığı nedeniyle, bildirilmiş bir oran bulunmamaktadır. Bu yazıda ameliyat edilen iki Amyand hernili olgu sunuldu. Birinci olgu yenidoğan döneminde ultrasonografi ile strangüle Amyand hernisi tanısı konularak ameliyat edildi. İkinci olgu, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Some surgeons prefer to protect the appendix when it is not inflamed, whereas others routinely perform an appendectomy through the sac. 9 There have been three pediatric series of Amyand's hernia. 10 Kaymakci et al 11 reported on a series of 30 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons prefer to protect the appendix when it is not inflamed, whereas others routinely perform an appendectomy through the sac. 9 There have been three pediatric series of Amyand's hernia. 10 Kaymakci et al 11 reported on a series of 30 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Amyand’s hernia (AH), is the rare presence of appendix in the inguinal hernial sac [1], has an estimated incidence of 1% of all inguinal hernias [2]. The clinical picture of AH depends on whether the appendix progresses to inflammation (≈0.1% of appendicitis cases) [3], or is further incarcerated leading to strangulation and perforation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The hernia is characterized by the presence of appendix vermiformis in the inguinal hernial sac [1], [2]. The incidence of AH is estimated as 1% of all inguinal hernias [3].…”
Section: Introductionmentioning
confidence: 99%